Apoio social na vivência do período gravídico-puerperal percebido pela puérpera adolescente - Cremonese, Luiza (2017)
The puerperal stage when experienced by a teenager can be intensified since the puerperal phase as well as the adolescence involves a period of physical, socio-cultural and body changes. Thus, it's very important to provide social support to teens who have recently given birth, come that support from family, friends, partner, school or health centers. Therefore, this study research question is: "What are the perceptions of recent teen mothers about the social support received?" And the objective is to know the perception of recent teen mothers about the social support received. This is a descriptive field study with a qualitative approach. The study scenario was Santa Maria's University Hospital (UFSM). The participants were 11 teenagers who have recently given birth. For the data collection semi-structured interviews and the speaking map dynamics were used, it happened from May to August, 2016. Minayo's operative proposal was chosen for the data analysis. The ethical aspects of the resolution 466/12 of the National Council of Health by the Ministry of Health were followed. The research was approved in the UFSM Research Ethics Committee, according to the docket 1,538,235, under the number of the CAAE 53932116.0.0000.5346. The fulfillment of this study allowed to learn the experience of the teenagers during the pregnancy and postpartum period and the kinds of social support that were offered to them. The teenagers upon having a child had to rearrange their lives, got alienated and suffered some losses, some got frustrated with the lack of support and other managed to overcome the difficulties while counting on the different kinds of support. The results of this study are presented in two scientific articles entitled: Experiences of the pregnancy and postpartum period under the perspective of teen women; Social support under the perspective of teens who have recently given birth. This research emphasizes the importance of the social support offered to teens in their becoming a mother process. The professionals encouraging the participation of the members of the teens's social support network in the process is very important, considering it as a possibility of health promotion.